USO DO HERBICIDA GLIFOSATO NAS LAVOURAS MARANHENSES: uma análise fundamentada na teoria da sociedade de risco. - BARROS, Juliana Almeida (2017)
The purpose of this dissertation is to analyze current society, from the point of view of the study of the theory of risk society developed by the sociologist Ulrick Beck. This theoretical framework allows us to reflect on the challenges that a global society of risks, where pesticides appear as one of the protagonists, imposes on society as a whole, with a special focus on Maranhão society, as well as on the environment, considering the scientific uncertainties about the future consequences that these products may cause. Such an analysis is relevant because of the contemporary environmental problems arising from the modernization process, which are capable of producing risks affecting the whole world. Among these risks that accompany technical-scientific development, there are those from agricultural activities, focusing on the worldwide emergence and spread of the herbicide glyphosate, which is currently one of the most used pesticides in the world and the most used in the Brazilian agriculture. This pesticide is the result of the most up-to-date technological innovations in relation to weed control. However, despite its large scale use, it is involved in a number of controversies regarding its impacts on human health and the environment, posing risks as such unpredictability arises. In addition, it is perceived that the predominance of the herbicide in Maranhão agriculture without the existence of public policies aimed at guaranteeing the right of information to the agricultural producer and the population in general, and the guarantee of the right to the environment ecologically balanced may result in actions of disrespect to the basic principles brought by the Federal Constitution, as it violates the right of citizens to decide, according to their most intimate feelings, whether to use this pesticide or not, and whether to choose foods treated with it or not, maintaining several producing sectors exposed to the risks and uncertainties that may cause serious consequences. The proposed study has a contribution to the academic, social and legal field, since the emergence of new technologies, such as agrochemicals, and more specifically glyphosate, lead to several issues involving economic, environmental, public health issues, among others, on which there are heated and provocative debates.